Factors Associated with Exclusive Breastfeeding among Mothers in Rural Chattogram of Bangladesh - Alam, Md Shah; Nahar, Kamrun; Chowdhury, Muhammad Jabed Bin Amin; Das, Aparup Kanti; Chowdhury, Dhiman; Barua, Dazy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Exclusive Breastfeeding (EBF) is recommended for the first six months of age by the World Health Organization (WHO). Mothers' good knowledge and positive attitude play key roles in the process of EBF practices. The study aimed to assess maternal knowledge, attitudes, and other factors associated with EBF practices in a rural area of Chattogram, Bangladesh. Materials and methods: This descriptive cross-sectional study was conducted in two rural private hospital outpatient departments in Lohagara, Chattogram, Bangladesh, during the COVID-19 pandemic from July 2021 to December 2021. Two hundred and forty mothers with children of age 6 to 24 months selected by purposive sampling were interviewed using a questionnaire to elicit information on infant breastfeeding practices and their associated factors. Data were collected throughthe face-to-face interview from hospital's outdoors, following a convenient sampling method. Chi-squared test and binary logistic regression models were used to explore the association. Results: The prevalence of EBFfor the first six months of an infant's life was 64.6%. Good knowledge (p<0.001) and a positive attitude (p<0.001) toward breastfeeding were significantly associated with EBF practices. A binary multivariable logistic regression model demonstrated that for mothers with SSC or higher-level education (AOR=3.21, 95% CI: 1.20-13.14) family monthly income >50000 BDT (AOR=2.11, 95% CI: 1.04-15.23) normal delivery (AOR=1.99, 95% CI: 1.11-8.23) and hospital delivery (AOR=3.34, 95% CI: 1.67-10.11) mothers were more likely to follow EBF practices compared to their counterparts. Moreover, joint family (AOR=0.32, 95% CI: 0.15- 0.68) and younger mother (AOR=0.42, 95% CI: 0.45-0.99) mothers had less likelihood of EBF practices than their counterparts. Conclusion: One in every three children in the study sitedoes not breastfeed exclusively, which needs special attention from the policymakers.Besides good knowledge and a positive attitude, the most important predictors were modifiable factors for EBF; hence should be addressed to improve EBF practices. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 3-7